Endoscopic transpontin cisternostomy — access to large cistern of the brain as method for treatment of occlusive hydrocephaly, complicated by adhesive process in pontine cisterns - Danchin, A. A.; Polishchuk, M. E.; Danchin, A. G. (Ukrainian Neurosurgical Journal, 2010)
Results of endoscopic ventriculocisternostomy at 20 patients with occlusive hydrocephaly, caused by adhesive process of brain waterpipe, were analyzed. At 3 (15%) cases additional adhesive process in a field of pontine cisterns was revealed. For it’s elimination we proposed to perform an endoscopic operation for pontite cisterns connection with brain large cistern in area between VI and VII cranial nerves. Anatomic reference points of punching area and endoscopic anatomic structures of large brain cistern were given.